Activities of the Lithuanian Left-wing Intelligentsia on the Eve of the Occupation of Lithuania and during its First Days - Tamošaitis, Mindaugas (Genocidas ir rezistencija, 2006)
This study reviews the activities of the Lithuanian left-wing intelligentsia on the eve of the occupation of Lithuania, and during the days after the invasion of 15 June 1940, that is, following the collapse of the authoritarian regime of Antanas Smetona and as thousands of Soviet troops marched into the country. At that time the Lithuanian society was in conflict over the sudden changes within the state. The majority seemed to be lost, misinformed by their own government, without a clear understanding of what was happening. The pro-Soviet part of the society whose strongest force was the radical left-wing intelligentsia, welcomed Smetona’s ouster with exultation as a long-awaited "morning of freedom" which dawned with the collapse of a nearly fourteen-year dictatorship. Yet, it was not fully appreciated that the Lithuanian government was subverted by the manipulations of a foreign power. At the outset of the occupation, as they had in October 1939, the pro-Soviet left-wing intelligentsia welcomed the Soviet forces and believed in the proclamations announced by the occupiers. Comparing the activities of the Lithuanian left-wing intelligentsia just before the occupation and during the first days of the Soviet regime, almost no essential differences are apparent. The authoritarian regime of Antanas Smetona was condemned, blindly relying on the Soviets and their officially peaceful policy promoted in regard to Lithuania. One reason for this was due the close interpersonal relationships of some Lithuanian left- wing intelligentsia with Soviet diplomats residing in Lithuania, as well as their close ties to the local Lithuanian Communist Party. At the beginning of the occupation, the left-wing intelligentsia naturally gained success with the help of the Soviet authorities, and accepted positions within the highest pro-Soviet state institutions. The study concludes that while the occupation of Lithuania in June 1940 was carried out by the Soviets, the fault for the tragedy which followed also lies with some Lithuanians, primarily with the left-wing intelligentsia which from the very first day moved in step with the new masters of Lithuania.